Degradation and Digestion of Polypropylene, Polyethylene, and Styrofoam by Tenebrio molitor L. (Coleoptera, Tenebrionoidae) Larvae - Subchan, Wachju; Rohman, Abdu; Prihatin, Jekti; Salma, Fahriyah Ulimatus; Halimah, Rohima Novianti; Jannah, Alifia Wardhatul; Rosita, Risa (Makara Journal of Science, 2024)
The increasing use of disposable plastic bags is affecting environmental problems because it requires thousands of years to degrade naturally. To overcome these problems, mealworms (larvae of Tenebrio molitor L.) become an alter-native solution. They can be considered as biodegradation agents of plastic because of the presence of symbiont bacte-ria in its gut that secretes plastic-depolymerizing enzymes. Therefore, this study aimed to compare the degradation and digestion ability of T. molitor in consuming various plastic types and thickness. Two designs have also been used: first, comparing the degradation and digestion of various plastic types, and second, comparing the degradation and diges-tion of various plastic bag thicknesses. The first design consists of three types of treatments, and the control group comprised three repetitions. The control group was fed with concentrate; treatment group 1 (P1), PP plastic bags; treat-ment group 2 (P2), high-density polyethylene (HDPE) plastic bags; and treatment group 3 (P3), styrofoam. The second design encompasses two treatment types, and the control group composed of repetitions. The control group was fed with concentrate; treatment group 1 (P1), HDPE plastic bags with a thickness 0.01 mm; and treatment group 2 (P2), HDPE plastic bags with a thickness of 0.02 mm. The result indicates that in the first design, the highest degradation and digestion occurred in treatment 3 (styrofoam) with an average of 0.001267 and 0.0063 fragment/individual, respective-ly. The second design the highest degradation occurred at P1 of 0.000009609 mg/day/individual. The highest digestion occurred at P1 with a total average of 0.004568 fragment/individual.